Optimization and Modeling of Microwave-Assisted Extraction of Curcumin and Antioxidant Compounds From Turmeric by Using Natural Deep Eutectic Solvents - Doldolova, Khadija; Bener, Mustafa; Lalikoğlu, Melisa; Aşçı, Yavuz Selim; ARAT, REFİK; Apak, Reşat (Elsevier Sci Ltd., 2021)
Natural deep eutectic solvents (NADES) have recently come to the fore as new green solvents for foods, cosmetics and pharmaceuticals due to their unique solvation power and low toxicity. Turmeric extracts were prepared using the microwave assisted extraction method (MAE) using five NADES containing binary combinations of choline chloride, lactic acid, fructose, and sucrose. The MAE method was optimized and modeled by using response surface methodology to obtain maximum total antioxidant capacity (TAC) and curcumin contents (CC) in extracts for each NADES. All NADES extracts, except NADES-1 containing fructose and cholin chloride, exhibited higher TAC and CC than those in 80% methanol:water which was the preferred solvent in literature. NADES solvents did not interfere with subsequent antioxidant capacity measurements using the CUPRAC method. The proposed MAE is a potentially efficient and sustainable procedure in pharmaceutical and food industries for the extraction of antioxidants and curcumin from turmeric.
🏆 Highly Cited Paper
Keywords: NADES; Turmeric; Antioxidants; Curcumin; Microwave Assisted Extraction